Comparison Of Effectiveness Benefits Of Providing Young Papaya Fruit Extract And Breast Care For Normal Postpartum Mother's Breast Milk Production: Systematic Review - Ewith Widya Mareta; Ari Suwondo; Imam Djamaluddin (Universitas STRADA Indonesia, 2020)
Background: The consumption of breast milk in Indonesia is still very concerning, the household health survey (SKRT) explains that in 2014 there was only 4-12% of breast milk coverage in urban areas. In 2015, the amount of formula feeding to babies aged 0-6 months was 16.7%, then increased in 2017 to 27.9%. Objective: To determine the comparison of the effectiveness of the benefits of giving young papaya extract and breast care to the production of normal postpartum mother's milk. Methods: This study uses the Systematic Review or Systematic Literature Review (SLR) method and uses the PRISMA protocol as data analysis. Results: The results of data analysis on the effectiveness of young papaya fruit extracts were more effective, with effect size values ​​of 1.02 and the 1.1 Conclusion: The provision of young papaya fruit extract is more effective against breast milk production.